Preparing Muhadatsah Material in Light of The Direct Method for Students of State Islamic University Purwokerto - Ade Ruswatie; Enjang Burhanudin Yusuf (UIN Siber Syekh Nurjati Cirebon, Indonesia, 2023)
Purpose: The objectives of this research is to provide production of muhadatsah material preparation in light of the direct method and to know the characteristics of muhadatsah material preparation in light of the direct method for students of the Department of Arabic Language Education at the State Islamic University of Purwokerto. Design/ methods/approach: This research used a qualitative and developmental approach, as the researchers used questionnaire, interview, observation, as well as testing to collect data. Findings: After conducting the research, they obtained the following research results: (1) The muhadatsah material was prepared in light of the direct method, consisting of 10 lessons, each lesson having dialogues and simple rules related to the specific topic. As for the vocabulary for difficult words, the researchers provided them with colorful pictures showing the meanings of the words. Because this method avoids using the mother tongue, rather it is necessary to use the language studied. (2) The characteristics of muhadatsah material in light of the direct method are avoiding the mother tongue when writing it and using the studied or target language when preparing it using clear images that show the content of the topics in it. (3) Preparing the muhadatsah material according to the direct method is effective given the difference between the post-test and the pre-test, which is 2.9149. Research implications: The findings of this study can be utilized by educators to inform their teaching practices, particularly those who instruct the muhadatsah subject. Furthermore, those who wish to conduct further research on the subject in the future will have a reference in the research results, which will consider the fundamentals of muhadatsah subject preparation.